Extremely strong Shoda pairs with GAP. (September 2016) - Bakshi, Gurmeet K.; Maheshwary, Sugandha
Abstract: We provide algorithms to compute a complete irredundant set of extremely strong Shoda pairs of a finite group G and the set of primitive central idempotents of the rational group algebra Q [ G ] realized by them. These algorithms are also extended to write new algorithms for computing a complete irredundant set of strong Shoda pairs of G and the set of primitive central idempotents of Q [ G ] realized by them. Another algorithm to check whether a finite group G is normally monomial or not is also described.